#### Thank you for registering.

One of our academic counsellors will contact you within 1 working day.

Click to Chat

1800-5470-145

+91 7353221155

CART 0

• 0
MY CART (5)

Use Coupon: CART20 and get 20% off on all online Study Material

ITEM
DETAILS
MRP
DISCOUNT
FINAL PRICE
Total Price: Rs.

There are no items in this cart.
Continue Shopping

# Given that P(A)=0.8, P(A/B)=0.8 , P(A∩B)=0.5, Find (i)P(A/AUB) Answer-32/37 (ii)P(A∩B/AUB) Answer-20/37

9 years ago

Dear Shaleen,

P(A)=0.8, P(A/B)=0.8 , P(A∩B)=0.5       Given

and we know that the conditional probability

P(A/B)= P(A∩B)/ P(B)   so we can find  P(B)= 5/8

from this we can find  P(AUB) = P(A)+P(B)-P(A∩B)

P(AUB) = 37/40

P(A/AUB) =  P(A(AUB)/ P(AUB)

as     P(A(AUB) =P(A)    set theory

so we get

P(A/AUB) = P(A)/ P(AUB)

P(A/AUB)=(8/10)/(37/40)

P(A/AUB)=32/37

2)

P(A∩B/AUB)= ( P(A∩B)(AUB))/ P(AUB)

P(A∩B)(AUB) =P(A∩B)

 P(A∩B/AUB)=  P(A∩B)/ P(AUB)
putting the values we get
 P(A∩B/AUB)= 20/37

Now you can win by answering the questions on Discussion Forum. So help discuss any query on askiitians forum and become an Elite Expert League askiitian.

jitender

9 years ago

Hi Shaleen,

P(A)=0.8, P(A/B)=0.8 , P(A∩B)=0.5

Now conditional Probability,

P(A/B)= P(A∩B)/ P(B)

Hence  P(B)= 5/8

Next, P(AUB) = P(A)+P(B)-P(A∩B)

So P(AUB) = 37/40

And, P(A/AUB) =  P(A∩(AUB)/ P(AUB) -------[as P(A∩(AUB) =P(A)]

So,

P(A/AUB) = P(A)/ P(AUB)

P(A/AUB)=(8/10)/(37/40)

P(A/AUB)=32/37

For the Next one,

P(A∩B/AUB)= ( P(A∩B)∩(AUB))/ P(AUB)

 P(A∩B)∩(AUB) =P(A∩B)  P(A∩B/AUB)=  P(A∩B)/ P(AUB)
Substituting the values from above,
 P(A∩B/AUB)= 20/37

That solves the two parts.

Hope that helps.

Best Regards,